PENGELOLAAN ZIS DI UPZIS NU CARE-LAZISNU KECAMATAN SECANG KABUPATEN MAGELANG - Yeny Fitriyani; M Pudail; Tajun Yuhsinun; Ahmad Fauzan (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
UPZIS NU Care-LAZISNU is a zakat management institution formed by a community organization, Nahdlatul 'Ulama (NU), at the 31st Nahdlatul 'Ulama (NU) Muktamar in Boyolali in 2004. This research aims to determine how the management system zakat, infaq, and sadaqah funds use all organizational resources at UPZIS NU Care-LAZISNU. This study uses a qualitative method that begins by reviewing existing phenomena related to the management of zakat, infaq, and sadaqah funds at UPZIS NU Care LAZISNU. The theory used in this study is the management theory put forward by A.F Stoner, who has described a theory of management. The results of this study indicate that the management of zakat, alms, and infaq funds through comprehensive stages, starting from the fundraising stage (fundraising), utilization and distribution, and reporting at UPZIS NU Care-LAZISNU Secang District, has been going well.